(untitled) (TAJ: Journal of Teachers Association, 2018)
Missed abortions are common and represent a significant gynaecological emergency workload. The search for a non invasive method with high success rate has led to the use of misoprostol. Most research into the use of misoprostol for the medical evacuation of missed abortion has concentrated on its effect after oral administration. Recent evidence suggested an improved efficacy of uterine evacuation and a reduced incidence of side-effects if misoprostol was administered vaginally. The present study has been designed to compare the safety and efficacy of oral versus vaginal misoprostol for medical management of missed abortion. The present study was experimental and randomized. A total of 100 women with pregnancies of < 12 weeks from last menses (verified by ultrasound) were recruited for the study. Eligible women were allocated randomly to the two treatment groups by means of lottery. The primary outcome was measured by complete expulsion rate. The secondary outcome measure was patient’s side effects and satisfaction. The following variables were compared: complete or incomplete expulsion of the conceptus in 24 hours, induction expulsion interval time, side effects; dilatation of cervical canal in those patients who required surgical intervention, number of doses required, women’s perception and duration of hospital stay. The present study demonstrated that early expulsion of the product following induction, complete expulsion of the product after 24 hours, were significantly higher in the vaginal misoprostol group than those in the oral misoprostol group. The dose of misoprostol was also much lower in the vaginal group compared to the oral group. The need for surgical evacuation was markedly decreased in the vaginal group than that in the oral group. So, treatment of missed abortion by misoprostol through vaginal route should be explored for introduction into health care delivery system nation wide. TAJ 2011; 24(2): 106-110